2014
DOI: 10.1093/ntr/ntu174
|View full text |Cite
|
Sign up to set email alerts
|

Effects of User Puff Topography, Device Voltage, and Liquid Nicotine Concentration on Electronic Cigarette Nicotine Yield: Measurements and Model Predictions

Abstract: Introduction: Some electronic cigarette (ECIG) users attain tobacco cigarette-like plasma nicotine concentrations while others do not. Understanding the factors that influence ECIG aerosol nicotine delivery is relevant to regulation, including product labeling and abuse liability. These factors may include user puff topography, ECIG liquid composition, and ECIG design features. This study addresses how these factors can influence ECIG nicotine yield. Methods: Aerosols were machine generated with 1 type of ECIG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
341
4
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(389 citation statements)
references
References 33 publications
23
341
4
4
Order By: Relevance
“…For example, a high-voltage/low nicotine concentration combination can give the same or greater flux as a low-voltage/high nicotine concentration combination. 3 The flux, in turn, determines the effect of a given nicotine dose, ranging from no effect to acute toxicity. If ECIG nicotine flux is low, users likely will abandon the device as they would a passenger vehicle that has a top speed of 3 km/hr.…”
Section: Nicotine Fluxmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a high-voltage/low nicotine concentration combination can give the same or greater flux as a low-voltage/high nicotine concentration combination. 3 The flux, in turn, determines the effect of a given nicotine dose, ranging from no effect to acute toxicity. If ECIG nicotine flux is low, users likely will abandon the device as they would a passenger vehicle that has a top speed of 3 km/hr.…”
Section: Nicotine Fluxmentioning
confidence: 99%
“…3 For example, nicotine flux increases with longer puff duration and greater voltage and is unaffected by puff velocity. 3 The effect of product characteristics on nicotine flux can be represented by a "design efficacy index" (Z d ). Similarly, the ways that puff topography can influence nicotine flux can be represented by a puffing intensity parameter (Z p ).…”
Section: Nicotine Fluxmentioning
confidence: 99%
See 2 more Smart Citations
“…Surveys of dedicated EC users (which were all former smokers) have shown that high nicotine levels are important especially for the initiation of EC use. 3,4 Although nicotine delivery to the aerosol can be similar or higher than tobacco cigarettes, 5,6 clinical studies of EC use have shown that the nicotine absorption potential is significantly lower compared with tobacco cigarettes, even when new generation devices are used. 7 This is mostly attributed to the low speed of nicotine absorption, and clearly indicates that nicotine intoxication is highly unlikely when ECs are used as intended.…”
Section: Nicotine Delivery From Ecsmentioning
confidence: 99%